Konstruksi Penilaian Berbicara dalam Pembelajaran Bahasa Indonesia Kelas X SMAN di Kecamatan Tenayan Raya Pekanbaru - Hidayat, Rintani; Sukenti, Desi (UIR PRESS, 2021)
This research is based on the construction of speaking assessment in Indonesian language learning. The importance of this research is studied because it produces the basic concept of speaking assessment, especially in learning Indonesian SMA class X. The problem studied in this study is how the construction of speaking assessment in learning Indonesian for class X SMAN in Tenayan Raya District, Pekanbaru. The purpose of this study was to construct a speaking assessment in Indonesian language learning for class X SMAN in Tenayan Raya District, Pekanbaru. The main theory used by researchers is Kusumastuti (2019), Tarigan (2008), Yunus (2012) and A.K (2019). The research approach carried out using a qualitative approach. This type of research uses the type of field research. The research method uses the phenomenological method. The data analysis technique was carried out using phenomenological techniques. The data collection techniques used were in-depth interview techniques and documentation techniques. The research informants were class X Indonesian teachers at SMA Negeri 6 Pekanbaru, SMA Negeri 10 Pekanbaru, and SMA Negeri 11 Pekanbaru, totaling six teachers. Based on the analysis conducted by the researcher, the results of this study indicate that the assessment of speaking in learning Indonesian for class X at SMA Negeri 6 Pekanbaru, SMA Negeri 10 Pekanbaru, and SMA Negeri 11 Pekanbaru used forms, including (1) conversation, (2) ) pronunciation, (3) video, (4) intonation, (5) content, (6) reading, (7) practice, and (8) articulation. This study concludes that the eight forms of assessment found by researchers can be recommended to educational institutions as a concept for measuring student speaking assessment.